Implementation Of Arabic Language Learning Methods And Problem Solving In Teaching At Islamic Educational Institutions - Fathur Rusydi Amar (International Journal of Technology and Education Research, 2023)
Teaching Arabic is a process of teaching and learning (teaching) that functions to guide students towards more aspects of life that are faced by a person so that in expressing certain feelings and desires with Fusha Arabic both actively and passively. Teaching is a conscious effort from one person to another in the process of presenting language with systematic and directed lessons and the person being taught can change himself towards maturity both physically and spiritually. As socio-cultural, Arabic is certainly different from the socio-cultural of the Indonesian nation. This also raises problems with regard to learning Arabic. Due to these socio-cultural differences, there are differences between Arabic and Indonesian , including expressions, terms or names of objects. The problem that may arise is that Indonesian students who do not know the socio-cultural aspects of Arabic language do not understand the meaning easily and quickly.